[60]Fullerene-peptides: bio-nano conjugates with structural and chemical diversity. (1st November 2016) - Barron, Andrew R.
Abstract: [60]Fullerene-peptides represent a simple yet chemically diverse example of a bio-nano conjugate. The C60 moiety provides the following attributes to the conjugate: (a) precise three-dimensional architecture, (b) a large hydrophobic mass and (c) unique electronic properties. Conversely, the peptide component provides: (a) structural diversity depending on the overall length and amino acids composition, (b) charge flexibility and (c) secondary structure and recognition. Recent advances in the synthetic strategy for [60]fullerene-peptide synthesis from both pre-formed peptides and using solid phase peptide synthesis (SPPS) are described. The effects of the hydrophobic C60 on the secondary structure of the peptide depend on the sequence of the latter, but in general the relative stability of particular structures is greatly enhanced. The ability of the [60]fullerene substituent to dramatically modify both cellular uptake and transdermal transport is discussed as is the effects on cell viability and antimicrobial activity.